Development of e-MBO performance assessment model to improve the employee performance - Herawati, Yusleli; Asfitri, Melisa Kurnia; Junianto, Mahmud; Amalia, Adhisti; Azzahra, Nadia; Salsabila (Insight: Jurnal Ilmiah Psikologi, 2024)
Manual performance appraisal techniques are not adaptive to developments in information technology, and this is considered a flaw. This study aims to create and evaluate the e-MBO performance assessment system. This study was conducted in The Palembang Therapy Center (PTC). The sample consisted of 21 employees who were selected using purposive sampling techniques. Employees who have been working for at least a year were the inclusion criteria. Furthermore, this study uses a research and development (R&D) methodology referring to the Richey & Klein concept, consisting of model development, internal validation, and external validation. The R&D results found that there were no issues when using the e-MBO employee performance assessment approach. Therefore, the research hypothesis stating that the e-MBO instrument effectively assesses employee performance is accepted. Furthermore, effective implementation of e-MBO can improve employee performance. The e-MBO assessment system can enhance employee performance through improved accuracy, discipline, work quality, and technical skills. Keyword: e-MBO; performance assessment; employee performance; employee; PTC.